Vocês vão sair a bem ou a mal: an examination of (im)polite forms of address online in european portuguese - Faria, Rita (2022)
This article examines forms of address in European Portuguese online and their potential to convey, or facilitate, verbal aggression. Departing from an incident at Bairro da Jamaica in the outskirtsof Lisbon,in January 2019,where police were filmed attackingresidents, two corpora are constituted based on comments left on YouTube and online Portuguese broadsheets. The analysis of the data shows that forms of address are important devices to facilitate verbal aggression and impoliteness; that online platforms cannot be seen homogeneously but rather as specific contexts imposing specific discursive constraints; and that issues of identity and cognition are fundamental aspects to be developed in future research attempts into forms of address